Heat shrinkable label roll
The heat-shrinkable label addresses the issues of solvent penetration and peel strength by using a solvent composition with organic solvents and resins, ensuring high peel strength and preventing solvent penetration, even in high-speed processes.
Patent Information
- Application Number
- JP2023187628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-04-12
- Filing Date
- 2023-11-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2038-03-23
AI Technical Summary
Conventional heat-shrinkable labels face issues with solvent penetration and inconsistent peel strength, especially when used in high-speed tubing processes with thin films, leading to functional failures and waste.
A heat-shrinkable label formed by bonding the ends of a heat-shrinkable polyvinyl chloride or polystyrene film using a solvent composition that includes a combination of organic solvents like THF, MEK, or ethyl acetate, and resins such as polyester, polypropylene, or hydrogenated petroleum resin, ensuring high peel strength and preventing solvent penetration.
The solution provides heat-shrinkable labels with stable, high peel strength and prevents solvent penetration, even in high-speed tubing processes, ensuring the labels maintain their tubular shape and functionality.
Smart Images

Figure 0007662011000001 
Figure 0007662011000002 
Figure 0007662011000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-shrinkable label formed by rolling a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film into a tubular shape and bonding both ends of the film together with a solvent. More specifically, the present invention relates to a heat-shrinkable label in which excessive penetration of a solvent into the solvent-bonded parts is unlikely to occur even if the film that forms the label is thin. [Background technology]
[0002] Since the heat shrinkable film has a function of shrinkability, it can be laminated and integrated with an object by the shrinkage force and shapeability of the film itself without using fixing means such as adhesives or fasteners. Therefore, it has functions such as bundling and sealing as well as mechanical protection of the object by lamination or covering. Furthermore, if the heat shrinkable film itself has a special function, the special function can be added to the object by lamination. This property is effectively used in the packaging field, where the main purpose is protection during storage and distribution of the object, and imparting display and design. For example, it is used for covering, bundling, exterior, or sealing of various containers such as bottles including glass and plastic bottles, cans, and long objects such as pipes, rods, wood, various rod-shaped objects, or sheets. Specifically, it is used for covering a part or the whole of the cap, shoulder, and body of a bottle for the purpose of display, protection, bundling, and improving the commercial value by functionalization. Furthermore, it is also used for packaging multiple items such as boxes, bottles, plates, rods, and notebooks, as well as for packaging items by attaching a film to the item (skin packaging). In this case, if the film is given a display or design shape in advance, it becomes a product called a label.
[0003] Materials used for heat-shrinkable films include polyvinyl chloride, polystyrene, polyester, polyamide, aliphatic polyolefins and their derivatives, and rubber hydrochloride. Usually, films made of these materials are formed into a tube shape, and then, for example, they are placed on bottles or pipes are assembled, and then heat-shrunk for packaging or bundling. However, all conventional heat-shrinkable films have poor heat resistance and cannot withstand boiling or retorting at high temperatures, so when used for food, sanitary products, or pharmaceutical applications, they have the disadvantage of being unable to be sterilized at high temperatures. For example, when retorting, conventional films have the problem of being easily damaged during the process.
[0004] In the case of conventional heat-shrinkable films, films made of polyester-based resins are excellent in heat resistance, dimensional stability, solvent resistance, etc., but in order to achieve the desired heat shrinkage characteristics, adhesion, etc., precise control of manufacturing conditions is required, which poses problems such as cost.
[0005] Furthermore, due to the usefulness of heat-shrinkable films, they are now being used in fields where non-heat-shrinkable films and labels have traditionally been used. In particular, many labels for beverage containers have been replaced with heat-shrinkable labels, replacing stick-on labels made of paper or non-heat-shrinkable films. In particular, in the field of labels for plastic bottle containers, the use of heat-shrinkable labels is becoming more common, in part due to the issue of recycling, and a variety of packaging design forms and methods are being implemented. Among heat-shrinkable films, polyvinyl chloride-based shrinkable films have extremely excellent heat-shrinkage properties and a small natural shrinkage rate, and polystyrene-based shrinkable films have low shrinkage stress and a high shrinkage rate. is widely used.
[0006] However, since heat-shrinkable labels become waste after use, there has been a recent need to reduce the amount of waste from an environmental perspective, and thinner heat-shrinkable labels (thinner heat-shrinkable labels) are beginning to be used. Incidentally, in order to form a tubular label from a heat-shrinkable film, it is necessary to overlap and fix one end of the film in the width direction to the other end. Conventional methods for this fixing include a solvent adhesion method (Patent Documents 1 and 2) and a method using an adhesive (Patent Document 3). Among these, the solvent adhesion method is widely used because it allows processing into a tubular label at high speed.
[0007] In the process (tubing process) where heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film is joined together to form a tubular label using this solvent bonding method, the speed is being increased in order to improve production efficiency and reduce costs. In order to stably obtain solvent-bonded joints with high peel strength (adhesive strength) in the high-speed tubing process, tetrahydrofuran (THF), methyl ethyl ketone (MEK), or ethyl acetate are generally used as the adhesive solvent. However, with THF, MEK, and ethyl acetate, in the case of thin heat-shrinkable polyvinyl chloride films or heat-shrinkable polystyrene films that contain a lot of amorphous raw materials, the solvent penetrates from the coated side to the back side of the film (solvent penetration), and the solvent also adheres to the back side. As a result, when the tubular label after solvent bonding is wound into a roll, the tubular label is crushed flat, but if solvent penetration occurs in the solvent-bonded part, the label that comes into contact with the back side of the solvent-bonded part will adhere, and it will no longer function as a tube, or blocking will occur, making it impossible to unravel the roll.
[0008] On the other hand, if the amount of THF, MEK, or ethyl acetate applied is reduced to prevent the solvent from penetrating through, the amount of solvent applied is prone to variation in the high-speed tubing process, and if the amount applied is reduced, sufficient peel strength cannot be obtained. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 3075019 [Patent Document 2] Patent No. 3452021 [Patent Document 3] JP 2014-43520 A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a heat-shrinkable label and packaging material having a solvent-bonded part that does not cause solvent penetration even when the film is thin, and in particular, to provide a heat-shrinkable label and packaging material having a solvent-bonded part that can provide a stable high peel strength even in a high-speed tubing process. [Means for solving the problem]
[0011] As a result of extensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using an adhesive solvent composition comprising a combination of specific types of compounds, and have thus completed the present invention. That is, the present invention has the following configuration.
[0012] 1. A tubular heat-shrinkable label in which both ends of a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film are bonded together with a solvent composition, wherein the solvent composition contains at least one organic solvent selected from the group consisting of tetrahydrofuran (THF), methyl ethyl ketone (MEK), and ethyl acetate, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin, and the peel strength of the adhesive joint is 2 N / 15 mm or more. 2. The heat-shrinkable label according to 1, wherein the resin contained in the solvent composition is polyester and the content of the resin is 5% by weight or more and 40% by weight or less. 3. A heat-shrinkable label according to 1, wherein the resin contained in the solvent composition is polypropylene or hydrogenated petroleum resin, and the content of the resin is 5% by weight or more and 40% by weight or less. 4. A heat-shrinkable polyvinyl chloride label according to any one of 1 to 3, wherein the heat-shrinkable polyvinyl chloride film or the heat-shrinkable polystyrene film has a thickness of 5 μm or more and 50 μm or less. 5. A package having the heat-shrinkable label according to any one of 1 to 4 above on at least a part of the outer periphery of an object to be packaged. 6. A method for producing a heat-shrinkable label, comprising overlapping and bonding both ends of a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film using a solvent composition containing at least one organic solvent selected from the group consisting of tetrahydrofuran (THF), methyl ethyl ketone (MEK), and ethyl acetate, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin. 7. A solvent composition for heat-shrinkable labels, which comprises at least one organic solvent selected from the group consisting of tetrahydrofuran (THF), methyl ethyl ketone (MEK), and ethyl acetate, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin, and is used to produce a heat-shrinkable label by adhering a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film with the solvent composition. Effect of the Invention
[0013] The present invention makes it possible to provide a heat-shrinkable label and a package having a solvent-adhesive portion that does not suffer from solvent penetration even when the heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film is thin, and that can provide a stable high peel strength even in a high-speed tubing process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The heat-shrinkable label of the present invention is a tubular heat-shrinkable label formed by overlapping both ends of a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film and bonding them with a solvent composition. Here, the end means the end in the width direction (direction along the longitudinal direction), and refers to a position including a portion within 20 mm from the end. The heat-shrinkable polyvinyl chloride film of the present invention includes not only a film consisting of a single layer of polyvinyl chloride, but also a laminated film having a laminated structure such as polyvinyl chloride / resin other than polyvinyl chloride / polyvinyl chloride, both of which are polyvinyl chloride films on the outside. The heat-shrinkable polystyrene film of the present invention includes not only a film consisting of a single layer of polystyrene, but also a laminated film having a laminated structure such as polystyrene / resin other than polystyrene / polystyrene, both of which are polystyrene films on the outside.
[0015] In the present invention, the adhesive solvent composition contains both at least one organic solvent selected from the group consisting of THF, MEK, and ethyl acetate, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin, so that a label can be provided that has high peel strength at the solvent-bonded portion and good solvent penetration, even in a high-speed tubing process.
[0016] THF, MEK, and ethyl acetate are all good solvents for polyvinyl chloride and polystyrene, and dissolve polyvinyl chloride and polystyrene films quickly, so the resulting solvent-bonded joints have high peel strength. However, they are not suitable for thin films because they are prone to solvent penetration. Also, if the amount of coating is reduced, the coating amount will vary and insufficient peel strength will occur during high-speed solvent bonding.
[0017] On the other hand, polyester can be suitably used as an adhesive because it is easily soluble in organic solvents or heat when it contains one or more monomer components that can become amorphous components. In addition, polypropylene with low stereoregularity or dicyclopentadiene / aromatic copolymer-based hydrogenated petroleum resins can also be suitably used as adhesives, so that high peel strength can be obtained even with a small amount of solvent, as described above.
[0018] Although the polyester, polypropylene or hydrogenated petroleum resin can be melted with heat and used as a hot melt adhesive to bond films, when bonding a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film, the heat of the hot melt agent causes the polyvinyl chloride film or the heat-shrinkable polystyrene film to shrink and wrinkle, which is likely to result in poor appearance. In addition, since the viscosity is high, it is difficult to stably apply a constant amount to the polyvinyl chloride film or the polystyrene film in a high-speed tubing process. That is, by containing at least one organic solvent selected from the group consisting of THF, MEK, and ethyl acetate, which are good solvents, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin, which functions as an adhesive, in the solvent composition, the above-mentioned drawbacks of each are covered, and it becomes possible to stably exhibit high peel strength even in a high-speed tubing process. Furthermore, even in a thin heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film, solvent penetration is unlikely to occur.
[0019] Examples of dicarboxylic acid components other than terephthalic acid that constitute the polyester used in the solvent composition of the present invention include aromatic dicarboxylic acids such as isophthalic acid, naphthalenedicarboxylic acid, and orthophthalic acid, aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid, and alicyclic dicarboxylic acids. Examples of diol components other than ethylene glycol that constitute the polyester used in the solvent composition include aliphatic diols such as 1,3-propanediol, 1,4-butanediol, neopentyl glycol, and hexanediol, alicyclic diols such as 1,4-cyclohexanedimethanol, and aromatic diols such as bisphenol A.
[0020] The polyester used in the solvent composition of the present invention is preferably a polyester containing one or more of aromatic dicarboxylic acids such as isophthalic acid, aliphatic dicarboxylic acids such as adipic acid, cyclic diols such as 1,4-cyclohexanedimethanol, and diols having 3 or more carbon atoms (for example, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, hexanediol, etc.) and having a glass transition point (Tg) of 70° C. or less.
[0021] In addition, the polyester used in the solvent composition has one or more monomer components that can be amorphous components in 100 mol % of the polyvalent carboxylic acid components or 100 mol % of the polyhydric alcohol components in the entire polyester resin at a total content of 30 mol % or more, preferably 40 mol % or more, more preferably 50 mol % or more. If the total content of the monomer components that can be amorphous components is less than 30 mol %, the solubility in the organic solvent is low and the polyester cannot be used as an adhesive solvent. Examples of monomers that can become amorphous components include isophthalic acid, orthophthalic acid, adipic acid, sebacic acid, 1,4-cyclohexanedimethanol, neopentyl glycol, 1,3-propanediol, 1,4-butanediol, and hexanediol.
[0022] The upper limit of the content of at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin contained in the solvent composition of the present invention is 40% by weight or less, preferably 37% by weight or less, and more preferably 34% by weight or less. The higher the content of the resin contained in the solvent composition, the higher the viscosity of the solvent composition becomes, and in a high-speed tubing process, it becomes difficult to stably apply the solvent composition to a polyvinyl chloride film in a constant amount. In addition, the lower limit of the content of the resin contained in the solvent composition is 5% by weight or more, preferably 8% by weight or more. If the content of the resin contained in the solvent composition is less than 5% by weight, the peel strength is insufficient when the amount of THF or the like applied is reduced.
[0023] The solvent composition of the present invention may contain various additives, such as a viscosity reducer, a heat stabilizer, a coloring pigment, a coloring inhibitor, and an ultraviolet absorbing agent, if necessary. Although there is no particular lower limit for the viscosity of the solvent composition, if the viscosity is too high, it becomes difficult to stably apply a constant amount in a high-speed tubing process, so the viscosity is preferably less than 100 mPa·s. The viscosity of the solvent composition is more preferably 80 mPa·s or less, even more preferably 60 mPa·s or less, and particularly preferably 50 mPa·s or less. In the tubing process, the solvent composition is applied to the heat-shrinkable polyvinyl chloride film or the heat-shrinkable polystyrene film in an amount of 50 to 550 mg / m 2 It is preferable to apply the adhesive solvent composition using a known center seal machine or the like to a width of about 1 mm. In addition, the application width of the adhesive solvent composition in the tubing process is preferably 1 mm or more in order to suppress peeling of the adhesive portion, and although there is no particular upper limit, it is preferable to apply the adhesive solvent composition to a width of 10 mm or less because the smaller the label area used, the lower the cost.
[0024] The speed of the tubing step is not particularly limited, but is preferably 300 to 500 m / min in terms of high speed. After the tubing step, the tubular label is usually folded flat and wound into a roll, and then the label is unwound and cut to a predetermined length to become a final product, but after the tubing step, a cutting step may be performed without winding onto a roll. The heat-shrinkable label of the present invention has a peel strength of 2 N / 15 mm or more at the solvent-bonded portion, preferably 3 N / 15 mm or more, more preferably 4 N / 15 mm or more. If the peel strength is 2 N / 15 mm or more, problems such as peeling during use can be prevented. The upper limit of the peel strength of the solvent-bonded portion is less than 10 N / 15 mm. Although a higher peel strength is preferable, a peel strength of 10 N / 15 mm or more could not be achieved in the present invention. The peel strength is measured according to the method described in the Examples.
[0025] The thickness of the heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film constituting the heat-shrinkable label of the present invention is preferably 5 μm or more and 50 μm or less. In order to meet the demand for thinner films, the thickness is more preferably 30 μm or less. The label may have a printing layer in a portion other than the adhesive portion. The heat shrinkable label of the present invention preferably has a heat shrinkage rate of 40% or more in the main shrinkage direction after immersing in 90°C hot water for 10 seconds. If the heat shrinkage rate is 40% or more, a beautiful shrinkage finish can be obtained. If it is less than 40%, the heat shrinkage force is insufficient, and when it is covered and shrunk around a container, it does not adhere to the container, resulting in poor appearance, which is undesirable. In the direction perpendicular to the main shrinkage direction, the heat shrinkage rate in 90°C hot water is preferably 15% or less. If it exceeds 15%, it is undesirable because a phenomenon called vertical sink, in which the label shrinks in the vertical direction, is likely to occur. The heat shrinkage rate in the main shrinkage direction means the heat shrinkage rate in the direction in which the sample shrinks the most, and the main shrinkage direction is determined by the length in the vertical or horizontal direction of a square sample. The method for measuring the heat shrinkage rate (%) follows the method described in the Examples.
[0026] The constitution of the polyvinyl chloride resin constituting the heat-shrinkable label of the present invention is not particularly limited as long as it can exhibit the heat-shrinkage characteristics described below, but examples thereof include polyvinyl chloride having a number-average polymerization degree of about 800 to 2500, preferably about 1000 to 1800, copolymers mainly composed of vinyl chloride (e.g., ethylene-vinyl chloride copolymer, vinyl acetate-vinyl chloride copolymer, vinyl chloride-halogenated olefin copolymer, etc.), or blends mainly composed of these polyvinyl chloride or vinyl chloride copolymers with other compatible resins (e.g., polyester resin, epoxy resin, acrylic resin, vinyl acetate resin, urethane resin, acrylonitrile-styrene-butadiene copolymer, partially saponified polyvinyl alcohol, etc.). These vinyl chloride resins may be obtained by any commonly used manufacturing method such as bulk polymerization, emulsion polymerization, suspension polymerization, solution polymerization, etc. These vinyl chloride resins may be used alone or in combination of two or more.
[0027] Conventionally, heat-shrinkable polyvinyl chloride resin films have usually contained a small amount of plasticizer in order to improve the flexibility of the film, the low-temperature shrinkability of the stretched film, and the fluidity and stretchability of the resin during extrusion processing.
[0028] Examples of the plasticizer used in the present invention include phthalic acid derivatives such as di-n-octyl phthalate, di-2-ethylhexyl phthalate, diisononyl phthalate, diisodecyl phthalate, and dicyclohexyl phthalate, isophthalic acid derivatives such as diisooctyl isophthalate, and adipic acid derivatives such as dioctyl adipate, as well as tricresyl phosphate, trixylenyl phosphate, and epoxidized soybean oil.
[0029] The above plasticizers may be used alone or in combination of two or more kinds, and are preferably contained in the heat-shrinkable polyvinyl chloride film in an amount of 20% by weight or more and 40% by weight or less, more preferably 25% by weight or more and 35% by weight or less.
[0030] In the present invention, various additive components, such as modifiers, heat stabilizers, fillers, ultraviolet absorbers, antioxidants, anti-tack agents, antistatic agents, colorants, etc., can be blended as desired within the scope of the present invention.
[0031] Examples of the modifier include methyl methacrylate-butadiene-styrene terpolymer (MBS resin), acrylonitrile-butadiene-styrene terpolymer (ABS resin), ethylene-vinyl acetate copolymer, chlorinated polyethylene, and the like. Examples of the heat stabilizer include organotin mercaptide-based, organotin maleate-based, organotin carboxylate-based, metal soap-based, lead-based, Ba-Zn-based, Ca-Zn-based, Ca-Zn-Ba-based, Ba-Mg-Al-based, epoxy compound-based, and chelators such as organic phosphite ester.
[0032] Examples of the filler include silica, talc, aluminum hydroxide, hydrotalcite, calcium sulfate, calcium silicate, calcium hydroxide, magnesium hydroxide, kaolin clay, mica, alumina, magnesium carbonate, sodium aluminate, and lithium phosphate. Examples of the ultraviolet absorber include benzotriazole-based, benzophenone-based, and salicylic acid-based ones.
[0033] The vinyl chloride resin composition for molding a heat-shrinkable polyvinyl chloride film of the present invention can be prepared by homogeneously blending the above-mentioned vinyl chloride resin, plasticizer and various additive components used as desired, each in a predetermined ratio, using a compounding machine or kneading machine such as a ribbon blender, a Banbury mixer, a Henschel mixer, a super mixer, a single-screw or twin-screw extruder, or a roll.
[0034] The composition of the polystyrene resin constituting the heat-shrinkable label of the present invention is not particularly limited as long as it can exhibit the heat-shrinkage characteristics described below, but it is preferably a polystyrene resin containing a polystyrene resin having a syndiotactic structure. More preferably, a polystyrene resin having a syndiotactic structure is used as the polystyrene resin. By using a polystyrene resin having a syndiotactic structure, mechanical strength and heat resistance are improved. By using such a polystyrene resin, in addition to the fact that the density of polystyrene is low and it is advantageous for separation in the recycling process, heat resistance, especially heat resistance during heated storage, is excellent, and the change in printing pitch caused by shrinkage over time after film formation is reduced, and high-precision printing can be performed as a label. Furthermore, durability against solvents contained in printing ink is improved, and printability is excellent.
[0035] The polystyrene resin having the above syndiotactic structure has a tacticity as determined by nuclear magnetic resonance spectroscopy of the phenyl groups and / or substituted phenyl groups in the side chains, which is preferably 75% or more, more preferably 85% or more in the case of a dyad (two constituent units), and preferably 30% or more, more preferably 50% or more in the case of a pentad (five constituent units).
[0036] The polystyrene component constituting the polystyrene-based resin used in the present invention may be polystyrene, poly(alkylstyrene)s such as poly(p-, m-, or o-methylstyrene), poly(2,4-, 2,5-, 3,4-, or 3,5-dimethylstyrene), and poly(p-tertiary butylstyrene), poly(halogenated styrene)s such as poly(p-, m-, or o-chlorostyrene), poly(p-, m-, or o-bromostyrene), poly(p-, m-, or o-fluorostyrene), and poly(o-methyl-p-fluorostyrene), poly(p-, m-, or o-methyl-p-fluorostyrene), Examples of suitable styrene-based copolymers include poly(halogenated alkylstyrenes) such as poly(p-, m-, or o-chloromethylstyrene), poly(alkoxystyrenes) such as poly(p-, m-, or o-methoxystyrene) and poly(p-, m-, or o-ethoxystyrene), poly(carboxyalkylstyrenes) such as poly(p-, m-, or o-carboxymethylstyrene), poly(alkyl ether styrenes) such as poly(p-vinylbenzyl propyl ether), poly(alkylsilylstyrenes) such as poly(p-trimethylsilylstyrene), and even poly(vinylbenzyl dimethoxyphosphide).
[0037] In the present invention, it is preferable to add a thermoplastic resin and / or a rubber component to the polystyrene resin. Examples of the thermoplastic resin include styrene resins such as polystyrene having an atactic structure, AS resin, and ABS resin, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamide resins such as nylon 6, nylon 66, nylon 12, nylon 4, and polyhexamethylene adipamide, and polyolefin resins such as polyethylene, polypropylene, and polybutene. On the other hand, as the rubber component, a rubber-like copolymer containing a styrene-based compound as its constituent component is preferred, and examples thereof include random, block or graft copolymers obtained by copolymerizing one or more types of styrene and rubber components. Examples of such rubber-like copolymers include styrene-butadiene copolymer rubber, styrene-isoprene block copolymer, rubbers in which the butadiene portion of these is partially or entirely hydrogenated, methyl acrylate-butadiene-styrene copolymer rubber, acrylonitrile-butadiene-styrene copolymer rubber, acrylonitrile-alkyl acrylate-butadiene-styrene copolymer rubber, and methyl methacrylate-alkyl acrylate-butadiene-styrene copolymer rubber. The rubber-like copolymer containing the above-mentioned styrene-based compound as its constituent component has a styrene unit, and therefore has good dispersibility in polystyrene-based resins having a syndiotactic structure, and has a large effect of improving the plasticity of polystyrene-based resins. In addition, as the compatibility adjuster, the above-mentioned rubber-like copolymer containing the above-mentioned styrene-based compound as its constituent component can be suitably used.
[0038] On the other hand, other examples of the rubber component that can be used include natural rubber, polybutadiene, polyisoprene, polyisobutylene, neoprene, ethylene-propylene copolymer rubber, urethane rubber, silicone rubber, acrylic rubber, polyether-ester rubber, and polyester-ester rubber.
[0039] The weight-average molecular weight of the polystyrene resin is preferably 10,000 or more, more preferably 50,000 or more. A weight-average molecular weight of less than 10,000 is not preferred because the strength and elongation properties and heat resistance of the film tend to decrease. There is no particular upper limit to the weight-average molecular weight, but a weight-average molecular weight of more than 1,500,000 is not preferred because breakage may occur due to an increase in the stretching tension. Polystyrene resins are commercially available in various grades from various manufacturers, and commercially available ones may be used. The other layer may be one layer or two or more layers.
[0040] The heat-shrinkable polyvinyl chloride film constituting the heat-shrinkable label of the present invention can be obtained by melt-extruding the above-mentioned polyvinyl chloride raw material with an extruder to form an unstretched film, and then transversely stretching and heat-treating the unstretched film by the following predetermined method. In the case of lamination, multiple extruders, feed blocks, or multi-manifolds may be used. When melt extruding the raw resin, the polyvinyl chloride raw material is melted at a temperature of 150 to 200° C. using an extruder and extruded into a film shape. Any existing method such as the T-die method or the tubular method can be used for extrusion. The extruded sheet-like molten resin can then be quenched to obtain an unstretched film. As a method for quenching the molten resin, a method in which the molten resin is cast from a die onto a rotating drum and rapidly cooled and solidified to obtain a substantially unoriented resin sheet can be suitably adopted. The obtained unstretched film is preheated at 80 to 120°C, preferably 90 to 110°C, if necessary, and then stretched in the transverse direction (direction perpendicular to the extrusion direction) by 3.0 times or more, preferably 3.5 to 7 times, using a tenter or the like. The stretching temperature is 70 to 110°C, preferably 80 to 100°C. After the transverse stretching, the film is preferably heat-treated at a temperature 1°C to 30°C higher than the stretching temperature. The heat treatment is carried out to relieve the tension in the film after stretching, and is effective in adjusting the heat shrinkage rate at the heat treatment temperature and reducing the natural shrinkage rate. This results in a heat-shrinkable polyvinyl chloride film that constitutes the heat-shrinkable label of the present invention.
[0041] The heat-shrinkable polystyrene-based film constituting the heat-shrinkable label of the present invention can be obtained by melt-extruding the above-mentioned polyester raw material with an extruder to form an unstretched film, and then stretching the unstretched film longitudinally and transversely and heat-treating it by a predetermined method described below. When laminating, multiple extruders, feed blocks, and multi-manifolds can be used. Generally, two or more types of chip-like polystyrene are mixed and used as the raw material for the film. When laminating, multiple extruders can be used. When melt extruding the raw resin, the polystyrene raw material is melted at a temperature of 200 to 250° C. and extruded into a film using an extruder. Any existing method such as a T-die method or a tubular method can be used for extrusion. The extruded sheet-like molten resin can then be quenched to obtain an unstretched film. As a method for quenching the molten resin, a method in which the molten resin is cast from a die onto a rotating drum and rapidly cooled and solidified to obtain a substantially unoriented resin sheet can be suitably adopted. The unstretched film obtained is heated with rolls at 70 to 100°C, preferably 80 to 90°C, as required, and then longitudinally stretched by 1.1 to 1.8 times using the roll speed difference. The longitudinally stretched film obtained is preheated at 80 to 120°C, preferably 90 to 110°C, as required, and then stretched in the transverse direction (direction perpendicular to the extrusion direction) by 3.0 times or more, preferably 3.5 to 7 times, using a tenter or the like. The stretching temperature is 70°C or more and 100°C or less, preferably 70°C or more and 95°C or less. After the transverse stretching, the film is preferably heat-treated at a temperature 1°C to 30°C higher than the stretching temperature. The heat treatment is carried out to relieve the tension in the film after stretching, and is effective in adjusting the heat shrinkage rate at the heat treatment temperature and reducing the natural shrinkage rate. This results in a heat-shrinkable polystyrene film that constitutes the heat-shrinkable label of the present invention.
[0042] The heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film of the present invention can be labeled by a conventional method. As an example, a heat-shrinkable polyvinyl chloride film or heat-shrinkable polystyrene film cut to a desired width is appropriately printed, and the left and right ends (both ends) of the film are overlapped and joined using the above-mentioned solvent composition to produce a tube film. This tube film is cut to an appropriate length to produce a tubular label. As an organic solvent for adhesion, at least one organic solvent selected from the group consisting of tetrahydrofuran (THF), methyl ethyl ketone (MEK), and ethyl acetate is an essential component, and in addition, aromatic hydrocarbons such as benzene, toluene, xylene, and trimethylbenzene, halogenated hydrocarbons such as methylene chloride and chloroform, phenols such as phenol, or mixtures thereof can be used. After perforations are formed in the label by a known method, it is placed on a PET bottle, and the PET bottle is placed on a belt conveyer or the like and passed through a shrink tunnel that blows steam (steam tunnel) or a shrink tunnel that blows hot air (hot air tunnel). The label thermally shrinks when passing through these tunnels, and the label is attached to the bottle container such as a PET bottle. The packaging body of the present invention is preferably formed by covering at least a part of the outer periphery of an object to be packaged with a label having a perforation or a notch obtained from the heat-shrinkable polyvinyl chloride film or the heat-shrinkable polystyrene film of the present invention and then heat-shrinking the label. Examples of the object to be packaged include PET bottles for beverages, various bottles, cans, plastic containers for sweets and lunch boxes, and paper boxes. In addition, when the label obtained from the heat-shrinkable polyvinyl chloride film is heat-shrunk to cover the object to be packaged, the label is usually heat-shrunk by about 5 to 70% to be attached to the packaging body. In addition, the label to be covered on the object to be packaged may or may not be printed. EXAMPLES
[0043] The present invention will be described in more detail below with reference to examples, but the following examples do not limit the present invention, and any modifications and variations within the scope of the present invention are included in the present invention. The physical properties of the films obtained in the examples and comparative examples were measured as follows. [Hot water heat shrinkage rate] The film was cut into a 10 cm x 10 cm square along the longitudinal direction and the perpendicular direction (width direction). It was then immersed in warm water at 90°C ± 0.5°C for 10 seconds under no load to cause it to heat shrink, and then immediately immersed in water at 25°C ± 0.5°C for 10 seconds. The sample was then pulled out of the water and the longitudinal and transverse lengths of the sample were measured. The value was calculated according to the following formula. Shrinkage rate = {(length before shrinkage - length after shrinkage) / length before shrinkage} x 100 (%) In this embodiment, the direction in which the film shrinks the most (main shrinkage direction) is the width direction. [Glass transition temperature (Tg)] The glass transition temperature was determined according to JIS K7121 using a differential scanning calorimeter (model: DSC220) manufactured by Seiko Denshi Kogyo Co., Ltd. 10 mg of unstretched film was heated from 25°C to 120°C at a heating rate of 10°C / min to obtain a heating profile. The glass transition temperature was determined as the temperature at the intersection of an extension of the baseline below the glass transition temperature and a tangent showing the maximum slope at the transition section.
[0044] [Solvent adhesion method] The film was cut to a width of 380 mm, and a film roll was produced with a longitudinal winding length of 1000 m. The film was unwound from the film roll, and the adhesive solvent composition was continuously applied to the inside of one end of the film in the longitudinal direction so that the application width was within a range of 4±2 mm. The part applied with the solvent composition was placed on the other end of the film in the width direction, and the film was folded over so that the overlapping part was at the center, and solvent bonded. The adhesive processing speed was 400 m / min, and the film after solvent adhesion was wound up on a paper tube at the same speed. The obtained tubular label roll was aged for 24 hours in an atmosphere of 23°C. The amount of the solvent applied is adjusted as desired. [Viscosity of adhesive solvent composition] The measurements were carried out using a Brookfield viscometer (model: BASE L) manufactured by Atago Co., Ltd., at an adhesive solvent composition temperature of 23° C. and a rotation speed of 10 rpm.
[0045] [Solvent penetration evaluation] The 1000m long tubular label obtained by solvent bonding was aged for 336 hours (14 days) in an environmental test room at 30℃ and 80% humidity. After that, 500m was pulled out from the roll surface, and if any blocking occurred, it was determined that the solvent had penetrated through, and was evaluated as follows: No blocking: Solvent penetration evaluation: ○ (no penetration) Blocking occurs: Solvent penetration evaluation × (penetration occurs)
[0046] [Method for measuring peel strength of solvent-bonded joints] During the above-mentioned solvent penetration evaluation, a sample with a width (equivalent to the longitudinal length) of 15 mm was cut out circumferentially from the surface of a tubular label roll with a winding length of 500 m after 500 m had been pulled out from the roll surface so that the solvent-bonded portion was in the center (the length should be about 100 mm). The number of samples n was 10. The samples were set in a Baldwin universal tensile tester "STM-50" and a 180° peel test was performed at a tensile speed of 200 mm / min. The average value of the 10 samples was taken as the peel strength (N / 15 mm) of the solvent-bonded portion.
[0047] <Synthesis examples of polyesters A to C> In a stainless steel autoclave equipped with a stirrer, a thermometer and a partial reflux condenser, 100 mol% of dimethyl terephthalate (DMT) as a dicarboxylic acid component and 100 mol% of ethylene glycol (EG) as a polyhydric alcohol component were charged so that the molar ratio of ethylene glycol was 2.2 times that of dimethyl terephthalate, and an ester exchange reaction was carried out using 0.05 mol% (relative to the acid component) of zinc acetate as an ester exchange catalyst while distilling off the produced methanol outside the system. Then, 0.225 mol% (relative to the acid component) of antimony trioxide was added as a polycondensation catalyst, and a polycondensation reaction was carried out at 280°C under reduced pressure of 26.7 Pa to obtain polyesters A, B and C shown in Table 2. In the table, TPA is terephthalic acid, IPA is isophthalic acid, AA is acrylic acid, SA is sebacic acid, EG is ethylene glycol, CHDM is 1,4-cyclohexanedimethanol, NPG is neopentyl glycol, and BD is 1,4-butanediol. The intrinsic viscosities of the polyesters in Table 2 were 0.53 dl / g for Polyester A, 0.98 dl / g for Polyester B, and 0.89 dl / g for Polyester C. Each polyester was appropriately cut into chips.
[0048] <Polypropylene and hydrogenated petroleum resin> The following polypropylene and hydrogenated petroleum resin were used. Polypropylene: Elmodu S-901, manufactured by Idemitsu Kosan Co., Ltd. Hydrogenated petroleum resin: Imerve (product name: P-140) manufactured by Idemitsu Kosan Co., Ltd.
[0049] <Method of manufacturing heat-shrinkable polyvinyl chloride film> A vinyl chloride resin composition for film molding was prepared by mixing 60% by weight of vinyl chloride resin (average degree of polymerization 1300), 30% by weight of phthalate ester plasticizer, 6% by weight of MBS resin, 2% by weight of barium-zinc composite stabilizer, 1% by weight of polymethyl methacrylate resin, and 1% by weight of ethylene bisstearic acid amide. The raw material formulation is shown in Table 1. The vinyl chloride resin composition was melt-extruded from the T-die of a single-screw extruder to obtain an unstretched film. The temperature of the extruder and the T-die was adjusted to 200°C. In addition, in order to stabilize the extrusion from the T-die, a helical type and parallel type gear pump was improved between the extruder and the T-die. At this time, the take-up speed of the unstretched film (the rotation speed of the metal roll) was about 20 m / min. The surface temperature of the metal roll was 20°C, and the thickness of the unstretched film obtained was about 75 μm. The unstretched film obtained was heated to 100°C in the preheating zone and stretched 5 times in the width direction in the stretching zone set at 80°C. It was then heat-treated at 88°C for 5 seconds and then cooled. Both edges were cut and removed, and the film was wound into a roll with a width of 500 mm, to continuously produce a uniaxially stretched film with a thickness of 15 μm over 1100 m. The obtained film was a heat-shrinkable polyvinyl chloride film that thermally shrinks only in the width direction. The hot water heat shrinkage measured at 90°C is shown in Table 3.
[0050] [Table 1]
[0051] [Table 2]
[0052] [Table 3]
[0053] [Example 1] The heat-shrinkable polyvinyl chloride film was coated with a solvent composition of THF / polyester A mixed at a weight ratio of 90 / 10 at a width of 4 mm at 300 mg / m2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 4. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 2] A tubular label roll was obtained in the same manner as in Example 1, except that the mixed solvent composition was a mixture of MEK and polyester A at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 4. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label. [Example 3] A tubular label roll was obtained in the same manner as in Example 1, except that the mixed solvent composition was a mixture of ethyl acetate and polyester A at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 4. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label. [Example 4] The heat-shrinkable polyvinyl chloride film was coated with a solvent composition of THF / polyester B mixed at 80 / 20 (weight ratio) at 300 mg / m 2 The coating was performed at a processing speed of 400 m / min. The tubular label roll was obtained by the above method. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were also measured, and the solvent bonding conditions and results are shown in Table 4. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 5] The heat-shrinkable polyvinyl chloride film was coated with a solvent composition of THF / polyester C mixed at a weight ratio of 95 / 5 at a width of 4 mm at a concentration of 300 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 4. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 6] The heat-shrinkable polyvinyl chloride film was coated with a 4 mm-wide solvent composition of ethyl acetate / polyester A mixed at a weight ratio of 60 / 40 at 100 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 4. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 7] The heat-shrinkable polyvinyl chloride film was coated with a solvent composition of ethyl acetate / polyester A mixed at 80 / 20 (weight ratio) at a thickness of 4 mm at 500 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 4. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0054] [Comparative Example 1] A tubular label roll was obtained in the same manner as in Example 6, except that only ethyl acetate was used as the adhesive solvent. The solvent adhesion conditions and results are shown in Table 4. The peel strength of the solvent-adhered portion was low, and the product was not suitable for use as a label. [Comparative Example 2] The heat-shrinkable polyvinyl chloride film was coated with ethyl acetate at 600 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded area were measured using the method described above, and the solvent bonding conditions and results are shown in Table 4. The peel strength of the solvent-bonded area was high, but there was solvent penetration (blocking), making it undesirable as a label. [Comparative Example 3] An attempt was made to obtain a tubular label roll in the same manner as in Example 1, except that a solvent composition in which THF / polyester C was mixed at a ratio of 40 / 60 (by weight) was used. The solvent adhesion conditions and results are shown in Table 4. The viscosity of the adhesive solvent composition was too high, so the adhesive solvent composition was applied to the film at a width of 4 mm and a concentration of 1 g / m 2 It was not possible to apply the coating as shown below.
[0055] [Table 4]
[0056] [Example 8] The heat-shrinkable polyvinyl chloride film was coated with a solvent composition of THF / polypropylene (S-901) mixed at a ratio of 90 / 10 (by weight) at a width of 4 mm at 300 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 5. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 9] A tubular label roll was obtained in the same manner as in Example 8, except that the mixed solvent composition was a mixture of MEK / S-901 at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 5. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label. [Example 10] A tubular label roll was obtained in the same manner as in Example 8, except that the mixed solvent composition was a mixture of ethyl acetate / S-901 at a weight ratio of 90 / 10. The solvent adhesion conditions and results are shown in Table 5. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label.
[0057] [Example 11] The heat-shrinkable polyvinyl chloride film was coated with a 4 mm-wide solvent composition of ethyl acetate / hydrogenated petroleum resin (P-140) mixed at a ratio of 95 / 5 (by weight), at a concentration of 300 mg / m 2The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 5. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 12] The heat-shrinkable polyvinyl chloride film was coated with a 4 mm-wide solvent composition of ethyl acetate / S-901 mixed at a ratio of 70 / 30 (by weight) at 300 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 5. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 13] The heat-shrinkable polyvinyl chloride film was coated with a 4 mm-wide solvent composition of ethyl acetate / S-901 mixed at a ratio of 70 / 30 (by weight) at 100 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 5. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0058] [Comparative Example 4] An attempt was made to obtain a tubular label roll in the same manner as in Example 1, except that a solvent composition in which THF / P-140 was mixed at a ratio of 40 / 60 (by weight) was used. The solvent adhesion conditions and results are shown in Table 3. Since the viscosity of the adhesive solvent composition was too high, the adhesive solvent composition was applied to the film at a width of 4 mm and a concentration of 1 g / m 2 It was not possible to apply the coating as shown below.
[0059] [Table 5]
[0060] <Method of manufacturing heat-shrinkable polystyrene film> After pre-drying the chips 1, 2, and 3 using a blender, the chips 1, 2, and 3 were continuously and separately fed into the mixing mixer using a fixed-volume screw feeder. The amount of chip 1 fed was 43 parts by mass, the amount of chip 2 fed was 43 parts by mass, and the amount of chip 3 fed was 14 parts by mass. The contents of the raw chips are shown in Table 1. Then, the mixed raw material of chips 1, 2, and 3 mixed in the mixing mixer was continuously and separately fed into a hopper directly above the extruder using a fixed-volume screw feeder. Then, the fed chips 1, 2, and 3 (already mixed) were melt-extruded from the T-die of a single-screw extruder. The temperature of the extruder was also adjusted to 200°C. In order to stabilize the extrusion from the T-die, a helical-type and parallel-type gear pump was interposed between the extruder and the T-die. The take-up speed of the unstretched film (the rotation speed of the metal roll) was about 20 m / min. The surface temperature of the metal roll was 20° C., and the thickness of the obtained unstretched film was 150 μm. The obtained film was heated with a metal roll having a surface temperature of 80° C., and then stretched 1.5 times in the longitudinal (machine) direction by using the speed difference of the rolls. Next, the obtained film uniaxially stretched in the longitudinal direction was heated to 100°C in a preheating zone and stretched 5 times in the transverse direction in a stretching zone set at 80°C. It was then heat-treated at 88°C for 5 seconds and then cooled. Both edges were cut and removed, and the film was wound into a roll with a width of 500 mm, to continuously produce a 20 μm-thick transverse uniaxially stretched film over 1100 m. The obtained film was a heat-shrinkable polystyrene-based film that thermally shrinks only in the transverse direction. The hot water heat shrinkage measured at 90°C is shown in Table 6.
[0061] [Table 6]
[0062] [Table 7]
[0063] [Example 14] The heat-shrinkable polystyrene film was coated with a solvent composition of THF / polyester A mixed at a weight ratio of 90 / 10 at a width of 4 mm at 250 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 8. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 15] A tubular label roll was obtained in the same manner as in Example 14, except that the mixed solvent composition was a mixture of MEK and polyester A at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 8. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label.
[0064] [Example 16] A tubular label roll was obtained in the same manner as in Example 14, except that the mixed solvent composition was a mixture of ethyl acetate / polyester A at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 8. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label. [Example 17] The heat-shrinkable polystyrene film was coated with a solvent composition of THF / polyester B mixed at 80 / 20 (weight ratio) at a width of 4 mm at 250 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 8. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0065] [Example 18] The heat-shrinkable polystyrene film was coated with a solvent composition of THF / polyester C mixed at a weight ratio of 95 / 5 at a width of 4 mm at 250 mg / m 2The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 8. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 19] The heat-shrinkable polystyrene film was coated with a 4 mm-wide solvent composition of ethyl acetate / polyester A mixed at a weight ratio of 60 / 40 at 100 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 8. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 20] The heat-shrinkable polystyrene film was coated with a solvent composition of ethyl acetate / polyester A mixed at 80 / 20 (weight ratio) at 400 mg / m 2 The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 8. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0066] [Comparative Example 5] A tubular label roll was obtained in the same manner as in Example 19, except that only ethyl acetate was used as the adhesive solvent. The solvent adhesion conditions and results are shown in Table 4. The peel strength of the solvent-adhered portion was low, making it unsuitable for use as a label. [Comparative Example 6] The heat-shrinkable polystyrene film was coated with ethyl acetate at 450 mg / m 2The solvent was applied so that the adhesive was bonded at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded area were measured using the method described above, and the solvent bonding conditions and results are shown in Table 4. The peel strength of the solvent-bonded area was high, but there was solvent penetration (blocking), making it undesirable as a label. [Comparative Example 7] An attempt was made to obtain a tubular label roll in the same manner as in Example 14, except that a solvent composition in which THF / polyester C was mixed at a ratio of 40 / 60 (by weight) was used. The solvent adhesion conditions and results are shown in Table 4. Because the viscosity of the solvent composition was too high, the solvent composition was applied to the film at a width of 4 mm and a concentration of 1 g / m 2 It was not possible to apply the coating as shown below.
[0067] [Table 8]
[0068] [Example 21] The heat-shrinkable polystyrene film was coated with a solvent composition of THF / polypropylene (S-901) mixed at a ratio of 90 / 10 (by weight) at a width of 4 mm at 250 mg / m 2 The solvent was applied so that the adhesive was adhered at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 9. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 22] A tubular label roll was obtained in the same manner as in Example 21, except that the mixed solvent composition was a mixture of MEK / S-901 at a weight ratio of 90 / 10. The solvent bonding conditions and results are shown in Table 9. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label.
[0069] [Example 23] A tubular label roll was obtained in the same manner as in Example 21, except that the mixed solvent composition was a mixture of ethyl acetate / S-901 at a weight ratio of 90 / 10. The solvent adhesion conditions and results are shown in Table 9. There was no penetration of the solvent, and the peel strength of the solvent-bonded part was high, making it a good label. [Example 24] The heat-shrinkable polystyrene film was coated with a 4 mm-wide solvent composition of ethyl acetate / polypropylene (P-140) mixed at a weight ratio of 95 / 5. 2 The solvent was applied so that the adhesive was adhered at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 9. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0070] [Example 25] The heat-shrinkable polystyrene film was coated with a 4 mm-wide solvent composition of ethyl acetate / S-901 mixed at a ratio of 70 / 30 (by weight) at 250 mg / m 2 The solvent was applied so that the adhesive was adhered at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 9. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label. [Example 26] The heat-shrinkable polystyrene film was coated with a 4 mm-wide solvent composition of ethyl acetate / S-901 mixed at a ratio of 70 / 30 (by weight) at 100 mg / m 2 The solvent was applied so that the adhesive was adhered at a processing speed of 400 m / min to obtain a tubular label roll. The presence or absence of solvent penetration and the peel strength of the solvent-bonded portion were measured using the above-mentioned method, and the solvent bonding conditions and results are shown in Table 9. There was no solvent penetration, and the peel strength of the solvent-bonded portion was high, making it a good label.
[0071] [Comparative Example 8] An attempt was made to obtain a tubular label roll in the same manner as in Example 1, except that an adhesive solvent composition in which THF / P-140 was mixed at a weight ratio of 40 / 60 was used. The solvent adhesion conditions and results are shown in Table 9. Since the viscosity of the adhesive solvent composition was too high, the adhesive solvent composition was applied to the film at a width of 4 mm and a concentration of 1 g / m 2 It was not possible to apply the coating as shown below.
[0072] [Table 9] [Industrial Applicability]
[0073] The heat-shrinkable label of the present invention has high peel strength at the solvent-bonded portion even when the amount of solvent varies during the process of bonding a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film to form a ring, and is less susceptible to solvent penetration (blocking), making it highly valuable in industry.
Claims
1. A tubular heat-shrinkable label roll in which both ends of a heat-shrinkable polyvinyl chloride film or a heat-shrinkable polystyrene film are bonded together with a solvent composition, the solvent composition containing at least one organic solvent selected from the group consisting of tetrahydrofuran (THF), methyl ethyl ketone (MEK), and ethyl acetate, and at least one resin selected from the group consisting of polyester, polypropylene, and hydrogenated petroleum resin, and the coating amount of the solvent composition in the bonded portion is 50 to 550 mg / m 2 and a peel strength of 2 N / 15 mm or more.
2. 2. The tubular heat-shrinkable label roll according to claim 1, wherein the resin contained in the solvent composition is polyester, and the content of the resin is 5% by weight or more and 40% by weight or less.
3. 2. The tubular heat-shrinkable label roll according to claim 1, wherein the resin contained in the solvent composition is polypropylene or hydrogenated petroleum resin, and the content of the resin is 5% by weight or more and 40% by weight or less.
4. 4. The tubular heat-shrinkable label roll according to claim 1, wherein the heat-shrinkable polyvinyl chloride film or the heat-shrinkable polystyrene film has a thickness of 5 μm or more and 50 μm or less.
Citation Information
Patent Citations
Heat-shrinkable polystyrenic resin film, and label and container using the same
JP2003094521A
Roll shrink label, container with roll shrink label, and method of manufacturing those
JP2012032657A
Heat shrinkable label, manufacturing method thereof, and container on which the label is attached
JP2013134446A
Hot-melt adhesive
JP2014043520A
METHOD FOR MANUFACTURING HEAT SHRINKABLE POLYESTER TUBE
JP3075019B2